Safety and Success of Repeat Lung Needle Biopsies in Patients with Epidermal Growth Factor Receptor‐Mutant Lung Cancer. (31st May 2019) - Fintelmann, Florian J.; Troschel, Fabian M.; Kuklinski, Martin W.; McDermott, Shaunagh; Petranovic, Milena; Digumarthy, Subba R.; Sharma, Amita; Troschel, Amelie S.; Price, Melissa C.; Hariri, Lida P.; Gilman, Matthew D.; Shepard, Joanne O.; et al.
Abstract: Background: Postprogression repeat biopsies are critical in caring for patients with lung cancer with epidermal growth factor receptor ( EGFR ) mutations. However, hesitation about invasive procedures persists. We assessed safety and tissue adequacy for molecular profiling among repeat postprogression percutaneous transthoracic needle aspirations and biopsies (rebiopsies). Materials and Methods: All lung biopsies performed at our hospital from 2009 to 2017 were reviewed. Complications were classified by Society of Interventional Radiology criteria. Complication rates between rebiopsies in EGFR ‐mutants and all other lung biopsies (controls) were compared using Fisher's exact test. Success of molecular profiling was recorded. Results: During the study period, nine thoracic radiologists performed 107 rebiopsies in 75 EGFR ‐mutant patients and 2, 635 lung biopsies in 2, 347 patients for other indications. All biopsies were performed with computed tomography guidance, coaxial technique, and rapid on‐site pathologic evaluation (ROSE). The default procedure was to take 22‐gauge fine‐needle aspirates (FNA) followed by 20‐gauge tissue cores. Minor complications occurred in 9 (8.4%) rebiopsies and 503 (19.1%; p = .004) controls, including pneumothoraces not requiring chest tube placement (4 [3.7%] vs. 426 [16.2%] in rebiopsies and controls, respectively; p < .001). The only major complication was pneumothorax requiring chest tube placement, occurring in zero rebiopsies and 38 (1.4%; p = .4) controls. Molecular profiling was requested in 96 (90%) rebiopsies and successful in 92/96 (96%). Conclusion: At our center, repeat lung biopsies for postprogression molecular profiling of EGFR ‐mutant lung cancers result in fewer complications than typical lung biopsies. Coaxial technique, FNA, ROSE, and multiple 20‐gauge tissue cores result in excellent specimen adequacy. Implications for Practice: Repeat percutaneous transthoracic needle aspirations and biopsies for postprogression molecular profiling of epidermal growth factor receptor ( EGFR )‐mutant lung cancer are safe in everday clinical practice. Coaxial technique, fine‐needle aspirates, rapid on‐site pathologic evaluation, and multiple 20‐gauge tissue cores result in excellent specimen adequacy. Although liquid biopsies are increasingly used, their sensitivity for analysis of resistant EGFR ‐mutant lung cancers remains limited. Tissue biopsies remain important in this context, especially because osimertinib is now in the frontline setting and T790M is no longer the major finding of interest on molecular profiling. Abstract : Repeated lung biopsy is important in caring for lung cancer patients with epidermal growth factor receptor (EGFR) mutations, but hesitation about the invasive procedure persists. This article assesses safety and tissue adequacy for molecular profiling among repeat post‐progression needle aspirations and biopsies.